SEXTUALLY ACTIVE: TEENAGE VIEWS ON SEXTING AND ITS INTERVENTIONS - Wade, Alex Christopher; Turner, Jerome; Weckesser, Annalise; Jørgensen Clara Rübner (AoIR Selected Papers of Internet Research, 2015)
The opportunities presented by digital mobile technologies to young people are extensive. These opportunities are countered by considerable challenges. These are especially evident in the sophisticated and commonplace practice of ’sexting’, the sharing of sexually explicit content via digital means. In the UK, child protection laws are such that the use of sexual images of minors (u-18) is a criminal offence, which has the paradoxical effect of potentially criminalising the people the law is meant to protect. Legislative issues are compounded by conflicting media commentary which confuses children and caregivers resulting in the practice of sexting being misunderstood. While some qualitative research has been undertaken into sexting, this has focussed on recommendations to caregivers, child welfare professionals and ISPs meaning young people’s position in forming constructive discourse has been minimised. Using qualitative data from participatory and interactive exercises with young people in a UK Midlands school, this project seeks to provide young people with a forum for exploring the impact of sexting on their daily lives, the role of digital technologies in enabling these practices to take place and the co-creation of tools to educate peers and professionals in the oversight of practice regarding sexting. The researchers on the project are from a multidisciplinary background and it is hoped that this will enable broad contribution to debates around education, sexual health and media usage.